Emotional intelligence and learning, and the role of ICTs - Chaidi , Irene; Drigas, Athanasios (Technium Social Sciences Journal, 2022)
The ability to understand one's feelings (emotional understanding) is an element and an important component of emotional intelligence. Understanding emotions are considered essential for the child's social and emotional functioning. This paper is a literature review of both the importance of socio-emotional learning in the child's life and emphasizes the role of parents and the school in its achievement.